2016
DOI: 10.1038/srep32507
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulator PrqR plays a negative role in glucose metabolism and oxidative stress acclimation in Synechocystis sp. PCC 6803

Abstract: Plant and cyanobacteria can perceive signals from soluble sugar and reactive oxygen species (ROS) and then coordinate gene expression under stress acclimation, but the underlying mechanism remains unclear. In this study, we found that the transcriptional factor PrqR (Slr0895) in Synechocystis can perceive signals from ROS generated after shifting from prolonged darkness with glucose into high-light. The deletion mutant (DprqR) showed increased growth rate and decreased ROS content, whereas the complementary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Hence, it is tempting to speculate that PrqR might be involved in the salt-stimulated expression of ggpS and other genes in this putative regulon. PrqR was reported as repressor for genes involved in glucose metabolism and oxidative stress acclimation [ 39 ]. The LexA protein, which is not changed on protein level but became significantly decreased on RNA level (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is tempting to speculate that PrqR might be involved in the salt-stimulated expression of ggpS and other genes in this putative regulon. PrqR was reported as repressor for genes involved in glucose metabolism and oxidative stress acclimation [ 39 ]. The LexA protein, which is not changed on protein level but became significantly decreased on RNA level (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Altered levels of the sigma factor sigE (sll1689), the sugar catabolism regulator Rre37 (sll1330), the negative regulator of glucose metabolism and oxidative stress acclimation PrqR (slr0895) and also PmgR1 (ncr0700) suggest an interesting link between CrhR and sugar/energy/heterotrophic metabolism, which is the major functional target category of these regulators [43][44][45][46][47]. PmgR1 (ncr0700), the most strongly induced sRNA in crhR TR , is involved in the switch to photomixotrophic growth and the regulation of glycogen metabolism [48].…”
Section: Altered Mrna Expression Correlates With Altered Cellular Mormentioning
confidence: 99%
“…Hence, it is tempting to speculate that PrqR might be involved in the salt-stimulated expression of ggpS and other genes in this putative regulon. PrqR was reported as repressor for genes involved in glucose metabolism and oxidative stress acclimation (Khan et al, 2016). The LexA protein, which is not changed on protein level but became significantly decreased on RNA level (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…S6). It has been recently shown that PrqR is involved in the acclimation to oxidative stress in Synechocystis 6803 (Khan et al, 2016). Salt stress is also inducing oxidative stress in cyanobacterial cells, hence, the finding of the role of PrqR in this stress acclimation process might of secondary importance.…”
Section: Discussionmentioning
confidence: 99%